SINONIMI BAHASA KABOLA DAN BAHASA HAMAP DI PULAU ALOR, NUSA TENGGARA TIMUR: SUATU KAJIAN DESKRIPTIF ANALISIS - Adhiti Ida Ayu Iran (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2020)
The study of local languages in Alor Island is needed in-depth. Local government efforts to foster and develop local languages have been made as an effort to preserve local languages. The research on the phenomenon of local languages in Alor Island is carried out by language experts. The study is discussed about Sinonimi and Hamap languages in Alor Island. The data collection of these two languages are analyzed with the theory of meaning relation. The data collection is compiled by listening and conversational methods, namely by listening to informant talks and inviting conversation. The data collection method is assisted with the interview method. This method id aimed to explore data optimally about several things in depth. Based on the analysis result, the vocabulary of Kabola and Hamap languages were found synonymy phenomenon. Vocabularies that have similarities and resemblance of these forms can be grouped into (1) synonymy by the removal and addition of vowel and consonant phonemes at the front and back positions of words; (2) synonymy with the relation of vowel and consonant phonemes in the middle and back positions of words; (3) synonymy with the relationship, addition, and omission of syllables in the first and second syllables; and (4) synonymy with the same absolute form or Iberian.